New type of PVC-membrane Ion-selective electrodes and their applicability to determine some antidepressand drugs - Wassel, Anwar A.; Abdullatif, Shabaan (Univerzita Pardubice, 2010)
The construction and electrochemical characterisation of potentiometric sensors of the PVC-membrane type are described being developed for the determination of selected antidepressants; namely: Olanzapine, Oxazepam, and Lorazepam. The sensing PVC-membranes incorporate the ion-associates of the drug cations with ammonium reineckate as selective materials dispersed in 2-nitrophenyl-octylether (NPOE) or dibutyl sebacate (DBS) as the plasticizers of choice. These ISEs exhibit rapid, stable and nearly Nernstian response over a relatively wide concentration range of 1×10–7 mol l–1-0.01 mol l–1 for Olanzapine and 1×10–6-0.01 mol l–1 for Oxazepam and Lorazepam, in mild acidic solutions with pH 4.5. No interferences caused by either inorganic or organic species were found. The three electrodes developed have been tested for potentiometric titrations of all three drugs, as well as for their direct determination via the respective calibration curves. The individual experiments then resulted in average recovery rates in an interval of 34 Wassel A.A., Abdullatif S./Sci. Pap. Univ. Pardubice Ser. A 16 (2010) 33–55 98.4-99.2 %, with the R.S.D. of ca. ±1.5 % (n = 3) for all three analytes of interest. Finally, the method proposed has been applied to the determination of the three drugs in pharmaceutical formulations and urine, when the results obtained were comparable to those obtained with the reference HPLC measurements.
Keywords: PVC-membrane; potentiometric titrations; HPLC measurements